Innate Immune Activation Can Trigger Experimental Spondyloarthritis in HLA-B27/Huβ2m Transgenic Rats - van Tok, Melissa N.; Satumtira, Nimman; Dorris, Martha; Pots, Desirée; Slobodin, Gleb; van de Sande, Marleen G.; Taurog, Joel D.; Baeten, Dominique L.; van Duivenvoorde, Leonie M. (Frontiers in Immunology, 2017)
Spondyloarthritis does not display the typical features of auto-immune disease. Despite the strong association with MHC class I, CD8+ T cells are not required for disease induction in the HLA-B27/Huβ2m transgenic rats. We used Lewis HLA-B27/Huβ2m transgenic rats [21-3x283-2]F1, HLA-B7/Huβ2m transgenic rats [120-4x283-2]F1 and wildtype rats to test our hypothesis that spondyloarthritis may be primarily driven by the innate immune response. In vitro, splenocytes were stimulated with heat-inactivated M. tuberculosis and cytokine expression and production was measured. In vivo, male and female rats were immunized with 30, 60 or 90 µg of heat-inactivated Mycobacterium tuberculosis and clinically monitored for spondylitis and arthritis development. After validation of the model we tested whether prophylactic and therapeutic TNF targeting affected spondylitis and arthritis. In vitro stimulation with heat-inactivated M. tuberculosis strongly induced gene expression of pro-inflammatory cytokines such as TNF, IL-6, IL-1a, and IL-1b, in the HLA-B27 transgenic rats compared to controls. In vivo immunization induced an increased spondylitis and arthritis incidence and an accelerated and synchronized onset of spondylitis and arthritis in HLA-B27 transgenic males and females. Moreover, immunization overcame the protective effect of orchiectomy. Prophylactic TNF targeting resulted in delayed spondylitis and arthritis development and reduced arthritis severity, whereas therapeutic TNF blockade did not affect spondylitis and arthritis severity. Collectively, these data indicate that innate immune activation plays a role in the initiation of HLA-B27-associated disease and allowed to establish a useful in vivo model to study the cellular and molecular mechanisms of disease initiation and progression.